Wind Engineering: Impact of Tornado on Low-rise building - Varshney, Monika; Shrivastava, Azad Kumar; Aggarwal, Alok; Kumar, Adarsh (International Journal of Computer Sciences and Engineering, 2018)
The effects of wind loading on buildings due to straight line boundary layer type winds have been studied extensively in the past. Building code estimates are mainly based on these works. Little research has been, however, done to study the effect of tornado winds on built structures. Despite the destructive effects of tornadoes, limited attempts have been made to quantify tornado induced loading. This paper essentially deals with the study of the effects of tornado type wind loading on low-rise buildings. Origin of winds and wind loads on buildings as per Indian IS:875 (Part -3) have been discussed and investigated in detail. Thrusted areas of research covering the impact of tornado on low-rise buildings have been discussed.